History of the Chaitanya Faith in Orissa - Mukherjee, Prabhat (Brill | Manohar Publishers & Distributors, 2023)
Vishambhar Misra, famously known as Chaitanya Mahaprabhu (c.1486-1534), led one of the most pioneering movements within the Vaishnava tradition in medieval India, which influenced many of the famous modern Hindu mystics, including Ramakrishna Paramahansa, and certain modern-day world famous Hindu mystical organizations like ISCKON. This book deals with Chaitanya Mahaprabhu's life and his version of Vaishnavaite mysticism in Orissa (presently Odisha). The author in the first part deals with the sources attributed to the Vaishnava saint written in Bengali, Odia, and Sanskrit during medieval and early modern periods. These include his biographies and mystical compositions dedicated to Lord Krishna composed by his followers. The second part deals with the religiosity and asceticism of the said saint, and how it is different from the traditional Vaishnavism practiced in medieval Orissa. The final part of this book deals with the impact of Mahaprabhu on the history of medieval Orissa and his movement prevalent in modern times. This book is highly recommended to those, who are interested in researching the history of Vaishnavism in medieval times, the history of Eastern India, and the study of Hinduism, in general.